The Potential for Plants to Remove Phosphorus from the Spodic Horizon - Debolina Chakraborty; Vimala D. Nair; Willie G. Harris; Roy D. Rhue (EDIS)
Under what conditions can plants be used to remove phosphorus from common Florida soils? This 5-page fact sheet shows how calculations for the phosphorus saturation ratio and soil phosphorus storage capacity at various soil depths can be used to determine whether to use phytoremediation as a strategy to remove phosphorus from the soil. Written by D. Chakraborty, V.D. Nair, W.G. Harris, and R.D. Rhue, and published by the UF Department of Soil and Water Science, October 2011.